Trends and Outcomes of Laparoscopic Surgery in Low‐Resource Settings: Lessons From Two African Healthcare Systems–A Narrative Review - Ali Emir Hamitoglu; Violette Fawaz; Shaima Omer Mohamed Elawad; Mohamad Monif Assker; Thea Maria Nader; Jack Wellington; Olivier Uwishema (Health Science Reports)
ABSTRACT Introduction Laparoscopic surgery (LS) has been a promising development in surgical practice globally ever since its introduction. LS has exhibited many an advantage, including bettering patient outcomes, lowering the risk of postoperative infection, and displaying economical affluence. However, its implementation in the African continent still faces various challenges. In this review, we investigated the status of laparoscopic surgery integration in Africa. Objectives In this review, we aimed to investigate the challenges posed by the implementation of LS in low resource countries as well as critically evaluating initiatives and their impact within said domiciles. We also provide recommendations that may assist in LS prosperity in these settings by focusing efforts on improving training and financial incentives. Methods A comprehensive literature review was conducted to garner up‐to‐date evidence concerning the fate of LS adoption in low‐ to middle‐income countries. This comprised the analysis of different case studies from countries including Nigeria and Botswana, and investigated relevant recommendations and policies provided by other African countries. Results Various challenges face the implementation of LS in countries with low resources comprising poor infrastructure, scarce training programs, and expert training personnel alongside financial boundaries. The adoption of LS in Africa has proved its benefits in improving patient outcomes and reducing hospital admissions. From a perspective of policy, it is crucial to sustain strong ties amongst institutions, stressing the importance of dynamic collaboration and locally tailored policies. Conclusion It has been demonstrated that LS implementations in African nations lower infection rates and expedite recovery. A strong collaboration between governments, stakeholders, and healthcare providers is fundamental for successful integration of LS. Such extension in low‐resource environments may be achieved by providing proper training programs, funding infrastructure and equipment, and fostering effective financial initiatives.